Comparing Mineral and Organic Nitrogen Fertilizer Impact on the Soil-Plant-Water System in A Succession of Three Crops - V. Sardo, M.A. Russo, A. Belligno, J.Y. Wu (Recent Research in Science and Technology, 2009)
In the belief that the investigation of the whole system helps to avoid the risk of incomplete or misleading responses resulting from the analysis of the single segments, a research was conducted in a succession of three crops (lettuce, red chicory and celery) to investigate in an integrated approach the different response of the soil-plant-water system to mineral and organic nitrogen fertilization. The experimental plan included the application of two amounts of fertilizer, corresponding to 240 and 360 kg ha-1 N under mineral or organic form per crop cycle, plus a control, in three replications. Mineral N resulted more promptly available to plants and increased the fresh and dry weight and protein content in leaves of the three crops while no significant difference in the tissue moisture content between the treatments was found. The inspection of combined data resulting from soil, plant and water analysis and from N budget demonstrates that altogether more mineral N was released in soil and water from the organic fertilizer while more N was uptaken by plants with the mineral fertilizer. Nitrogen uptake efficiency and N use efficiency in fact were highest in the mineral fertilized plots while surplus N was only found with the organic fertilization. Microbial population in the soil was unaffected by the type and amount of fertilizers; on the contrary, enzymatic activity responded positively to organic N while was depressed by the synthetic N form. The results suggest that the use of organic N integrated with mineral N at the appropriate crop stages is the solution to be recommended.